Meta-Analysis of Astragalus-Containing Traditional Chinese Medicine Combined With Chemotherapy for Colorectal Cancer: Efficacy and Safety to Tumor Response - Lin, Shuang; An, Xiaoxia; Guo, Yong; Gu, Jianzhong; Xie, Tian; Wu, Qibiao; Sui, Xinbing (Frontiers in Oncology, 2019)
This meta analysis evaluated the comparative safety and efficacy for the addition of Astragalus-based Chinese medicines combined with chemotherapy and chemotherapy alone for colorectal cancer (CRC) treatment. Systematic literature search was performed by PubMed, EMBSAE, Ovid, Web of Science, Cochrane Library, Chinese Science and Technology Journals (CQVIP), China Academic Journals (CNKI), and Chinese Biomedical Literature database. A total of 22 studies which reported on 1,409 subjects were identified. This meta-analysis indicated that the combination of Astragalus-based Chinese medicines and chemotherapy may increase the efficiency of tumor response rate (TRR) for the treatment of CRC patients (RR: 1.52; 95% CI: 1.24–1.87; p < 0.0001), improve their life quality based on KPS (RR: 2.51; 95% CI: 1.85–3.42; p < 0.00001 and WMD: 10.96; 95% CI: 9.45–12.47; p < 0.00001), and reduce the adverse reactions, including neutropenia (RR: 0.52; 95% CI: 0.44–0.62; p < 0.00001), anemia (RR: 0.49; 95% CI: 0.34–0.70; p < 0.0001), thrombocytopenia (RR: 0.59; 95% CI: 0.46–0.77; p = 0.0001), nausea and vomiting (RR: 0.56; 95% CI: 0.46–0.68; p < 0.00001), diarrhea (RR: 0.55; 95% CI: 0.40–0.75; p = 0.0001), and neurotoxicity (RR: 0.56; 95% CI: 0.49–0.65; p < 0.00001). Hepatic dysfunction (RR: 0.76; 95% CI: 0.53–1.09; p = 0.13) and renal dysfunction (RR: 0.95; 95% CI: 0.51–1.76; p = 0.87) were similar between two groups. The results showed that Astragalus-based Chinese medicines combined with chemotherapy in the treatment of CRC may increase the efficiency of TRR, reduce chemotherapeutic agents-associated adverse reactions, and improve their life quality when compared with chemotherapy alone, but further randomized studies are warranted.